Brief Report: Routine Use of Oral PrEP in a Phase 2 Rectal Microbicide Study of Tenofovir Reduced-Glycerin 1% Gel (MTN-017) - Albert Y. Liu (2019)
BACKGROUND: As daily oral preexposure prophylaxis (PrEP) becomes standard for HIV prevention, routine use of PrEP is likely to increase within clinical trials of novel preventive agents. We describe the prevalence and characteristics of participants reporting nonstudy oral PrEP use within Microbicide Trials Network-017 (MTN-017), a phase 2 trial of a rectal microbicide. SETTING AND METHODS: One hundred ninety-five HIV-uninfected men who have sex with men and transgender women were enrolled and followed in MTN-017 across 8 sites in the United States, Thailand, South Africa, and Peru from 2013 to 2015. Nonstudy oral PrEP use was recorded on case report forms and progress notes. Characteristics of PrEP users and non-PrEP users were compared using tests of statistical significance. RESULTS: Overall, 11% of participants reported nonstudy oral PrEP use, all from the San Francisco (SF) site, accounting for 58% (22/38) of participants enrolled in SF. There was a higher median number of sex partners reported in the past 8 weeks before enrollment among oral PrEP users vs. nonusers (7 vs. 2, P = 0.02). Most PrEP users (18/22, 82%) began PrEP treatment during screening/after enrollment, and most (19/22, 86%) decided to continue oral PrEP after study completion. CONCLUSION: Nonstudy oral PrEP use in the first phase 2 study of tenofovir reduced-glycerin 1% gel was high at a single site in SF where community PrEP availability and use was expanding. Investigators should consider the evolving context of nonstudy oral PrEP use across trial sites when designing and interpreting trials of novel biomedical prevention modalities.